An electrochemical device and a negative electrode sheet
Patent Information
- Application Number
- CN202510820894.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-18
- Publication Date
- 2026-10-20
AI Technical Summary
然而加入碳纳米管后,仅有少量的碳纳米管作用到了硅基材料与石墨材料之间,大部分碳纳米管作用到了石墨材料颗粒之间,对硅基材料与石墨材料之间的电接触改善效果不明显,电化学装置仍然存在循环衰减的问题
[0020]本申请中,分布在硅基材料颗粒与石墨材料颗粒之间的碳纳米管多于分布在石墨材料颗粒与石墨材料颗粒之间的碳纳米管,和/或,分布在硅基材料颗粒与硅基材料颗粒之间的碳纳米管多于分布在石墨材料颗粒与石墨材料颗粒之间的碳纳米管,表明碳纳米管主要分布在硅基材料颗粒表面上,碳纳米管的分布方式有利于碳纳米管构建硅基材料颗粒与硅基材料颗粒之间,特别是硅基材料颗粒与石墨材料颗粒之间的导电网络,由此有利于负极极片中的电子传导和离子传导,进而能够提高电化学装置的循环性能。此外,由于碳纳米管具有较好的柔韧性,从而有利于降低硅基材料颗粒体积膨胀而导致的碳纳米管脱落的概率,进一步有利于负极极片长久的维持高的电子传导和离子传导。
Smart Images

Figure BDA0005457236740000091 
Figure BDA0005457236740000101 
Figure BDA0005457236740000111
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical technology, specifically relating to an electrochemical device and a negative electrode plate. Background Technology
[0002] As market demand for energy density in electrochemical devices continues to increase, developing anode active materials is one of the key strategies for improving the energy density of electrochemical devices. Silicon-based materials, due to their high specific capacity, have been widely used to enhance the energy density of electrochemical devices. Because silicon-based materials have poor conductivity, while graphite materials have high conductivity, silicon-based materials are often used in combination with graphite materials in the anode electrode to achieve a balance between energy density and cycle performance of the electrochemical device.
[0003] However, silicon-based materials undergo significant volume expansion during lithium intercalation, much greater than that of graphite materials. This results in gaps between silicon-based and graphite materials during the cycling process of the electrochemical device, causing the electrical contact between the silicon-based and graphite particles to gradually disappear. Consequently, lithium ions in the silicon-based material cannot be properly intercalated and deintercalated, leading to accelerated degradation of the electrochemical device during cycling.
[0004] To address the issue of rapid degradation during cycling, existing technologies incorporate carbon nanotubes into the negative electrode, leveraging their excellent conductivity and high aspect ratio to construct a conductive network between the silicon-based and graphite materials. However, after adding carbon nanotubes, only a small amount interacts between the silicon-based and graphite materials; the majority interacts between the graphite particles, resulting in minimal improvement in the electrical contact between them. Consequently, the electrochemical device still suffers from cycling degradation.
[0005] Therefore, improving the cycle performance of electrochemical devices has become an urgent technical problem to be solved. Summary of the Invention
[0006] In view of this, the main objective of the present invention is to provide an electrochemical device and a negative electrode plate. This electrochemical device has improved cycle performance.
[0007] To achieve the above objectives, the technical solution of the present invention is implemented as follows:
[0008] A first aspect of the present invention provides an electrochemical device comprising an electrolyte, a positive electrode, and a negative electrode, wherein the negative electrode comprises a negative current collector and a negative electrode film disposed on at least one surface of the negative current collector; the negative electrode film comprises silicon-based material particles, graphite material particles, and carbon nanotubes; the carbon nanotubes distributed between the silicon-based material particles and the graphite material particles are more numerous than the carbon nanotubes distributed between the graphite material particles, and / or, the carbon nanotubes distributed between the silicon-based material particles are more numerous than the carbon nanotubes distributed between the graphite material particles.
[0009] In some embodiments, the mass fraction of carbon nanotubes is 0.01%-1%, based on the sum of silicon-based material particles and carbon nanotubes.
[0010] In some embodiments, the mass fraction of carbon nanotubes is 0.1%-0.5% of the total silicon-based material particles and carbon nanotubes.
[0011] In some embodiments, carbon nanotubes include one or more of single-walled carbon nanotubes, few-walled carbon nanotubes, and multi-walled carbon nanotubes.
[0012] In some implementations, the diameter of the carbon nanotubes is 0.4 nm to 3 nm.
[0013] In some embodiments, the silicon-based material particles include one or more of silicon oxides and silicon-carbon composites.
[0014] In some embodiments, the mass fraction of silicon-based material particles in the negative electrode film is 0.5%-10%.
[0015] In some embodiments, the negative electrode film layer further includes a conductive agent, wherein the mass fraction of the conductive agent in the negative electrode film layer is less than or equal to 3%.
[0016] A second aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector; the negative electrode film layer comprising silicon-based material particles, graphite material particles and carbon nanotubes; the carbon nanotubes distributed between the silicon-based material particles and the graphite material particles are more numerous than the carbon nanotubes distributed between the graphite material particles, and / or, the carbon nanotubes distributed between the silicon-based material particles are more numerous than the carbon nanotubes distributed between the graphite material particles.
[0017] In some embodiments, the mass fraction of carbon nanotubes is 0.01%-1%, based on the sum of silicon-based material particles and carbon nanotubes.
[0018] In some embodiments, the mass fraction of carbon nanotubes is 0.1%-0.5% of the total silicon-based material particles and carbon nanotubes.
[0019] In some implementations, the diameter of the carbon nanotubes is 0.4 nm to 3 nm.
[0020] In this application, the carbon nanotubes distributed between silicon-based material particles and graphite material particles are more numerous than those distributed between graphite material particles, and / or, the carbon nanotubes distributed between silicon-based material particles are more numerous than those distributed between graphite material particles. This indicates that the carbon nanotubes are mainly distributed on the surface of the silicon-based material particles. This distribution pattern facilitates the construction of a conductive network between silicon-based material particles, especially between silicon-based material particles and graphite material particles. This, in turn, is beneficial for electron and ion conduction in the negative electrode, thereby improving the cycle performance of the electrochemical device. Furthermore, due to the good flexibility of carbon nanotubes, the probability of carbon nanotube detachment caused by the volume expansion of silicon-based material particles is reduced, further contributing to the long-term maintenance of high electron and ion conduction in the negative electrode. Attached Figure Description
[0021] Figure 1 A schematic diagram of the structure of the negative electrode film prepared according to an embodiment of this application is shown.
[0022] Figure 2 A scanning electron microscope image of the negative electrode sheet prepared in Example 1 of this application is shown.
[0023] Figure 3 It shows Figure 2 A magnified view of a portion of region A in the middle.
[0024] Explanation of reference numerals in the attached figures:
[0025] 1. Negative electrode film; 101. Silicon-based material particles; 102. Carbon nanotubes; 103. Graphite material particles. Detailed Implementation
[0026] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, those skilled in the art...
[0027] All other embodiments obtained by a person skilled in the art without inventive effort are within the scope of protection of this invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0028] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0029] Unless otherwise specified, the term "or" is inclusive in this invention. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0030] Unless otherwise specified, in this invention, "one or more" or "at least one" refers to any one, any two, or any two or more of the listed items. "Several" refers to any two or more.
[0031] The first aspect of this application provides an electrochemical device. This electrochemical device can be a lithium-ion battery, a sodium-ion battery, a lithium metal battery, or a sodium metal battery; however, the embodiments of this application are not limited to this type.
[0032] Typically, an electrochemical device includes a positive electrode, a negative electrode, a separator, and an electrolyte. During the charging and discharging process, active ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.
[0033] The electrochemical device of this application includes an electrolyte, a positive electrode, and a negative electrode. The negative electrode includes a negative current collector and a negative electrode film disposed on at least one surface of the negative current collector. The negative electrode film includes silicon-based material particles, graphite material particles, and carbon nanotubes. The number of carbon nanotubes distributed between the silicon-based material particles and the graphite material particles is greater than the number of carbon nanotubes distributed between the graphite material particles, and / or the number of carbon nanotubes distributed between the silicon-based material particles is greater than the number of carbon nanotubes distributed between the graphite material particles.
[0034] In this application, the carbon nanotubes distributed between silicon-based material particles and graphite material particles are more numerous than those distributed between graphite material particles, and / or, the carbon nanotubes distributed between silicon-based material particles are more numerous than those distributed between graphite material particles. This indicates that the carbon nanotubes are mainly distributed on the surface of the silicon-based material particles. This distribution pattern facilitates the construction of a conductive network between silicon-based material particles, especially between silicon-based material particles and graphite material particles. This, in turn, is beneficial for electron and ion conduction in the negative electrode, thereby improving the cycle performance of the electrochemical device. Furthermore, due to the good flexibility of carbon nanotubes, the probability of carbon nanotube detachment caused by the volume expansion of silicon-based material particles is reduced, which is more conducive to maintaining high electron and ion conduction of the negative electrode for a longer period of time.
[0035] Furthermore, carbon nanotubes can primarily act on silicon-based material particles, thereby reducing the amount of carbon nanotubes added to the negative electrode, which is beneficial for further cost reduction.
[0036] Figure 1 This is a schematic diagram of the negative electrode film layer according to one embodiment of this application. In some embodiments, such as... Figure 1 As shown, in the negative electrode film layer 1, the negative electrode film layer 1 includes silicon-based material particles 101, carbon nanotubes 102, and graphite material particles 103. It can be seen that the carbon nanotubes 102 are mainly distributed between silicon-based material particles 101 and between silicon-based material particles 101 and graphite material particles 103. This facilitates the formation of a conductive network by the carbon nanotubes 102 between silicon-based material particles 101 and graphite material particles 102, and between silicon-based material particles 101 and silicon-based material particles 103, thereby improving electron and ion conduction in the negative electrode and enhancing the cycle performance of the electrochemical device.
[0037] In this application, the distribution state of carbon nanotubes can be tested in the following way: the negative electrode sheet is tested using a scanning electron microscope (SEM) to obtain its microstructure. From the SEM image of the negative electrode sheet, it can be observed that the carbon nanotubes are mainly distributed between silicon-based material particles and between silicon-based material particles and graphite material particles.
[0038] In some embodiments, the mass fraction of carbon nanotubes, calculated as the sum of silicon-based material particles and carbon nanotubes, is 0.01%-1%; alternatively, the mass fraction of carbon nanotubes is 0.1%-0.5%. A mass fraction of carbon nanotubes within the above range is beneficial for constructing conductive networks between silicon-based material particles and graphite material particles, as well as between silicon-based material particles themselves. This allows the silicon-based material particles to maintain electrical contact with the graphite material particles even after volume expansion, thereby improving the cycle performance of the electrochemical device. Exemplarily, the mass fraction of carbon nanotubes, calculated as the sum of silicon-based material particles and carbon nanotubes, is any value within the range of 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, or any combination thereof.
[0039] In some embodiments, carbon nanotubes include one or more of single-walled carbon nanotubes, few-walled carbon nanotubes, and multi-walled carbon nanotubes. Due to their excellent electrical conductivity and large aspect ratio, carbon nanotubes can easily form long-range conductive networks between silicon-based material particles and graphite material particles. This further reduces the probability of silicon-based material particles losing electrical contact with graphite material particles after volume expansion, and is more conducive to improving the cycle performance of electrochemical devices.
[0040] In some embodiments, the diameter of the carbon nanotubes is 0.4 nm to 3 nm. A diameter within this range reflects the small diameter of the carbon nanotubes. Small-diameter carbon nanotubes have high toughness and high dispersibility, which helps reduce the risk of carbon nanotube detachment caused by the expansion force of silicon-based material particles. For example, the diameter of the carbon nanotubes is 0.4 nm, 0.5 nm, 0.8 nm, 1 nm, 1.3 nm, 1.5 nm, 1.8 nm, 2 nm, 2.3 nm, 2.5 nm, 2.8 nm, 3 nm, or any value between two of these two values. The components of the electrochemical device are further described below:
[0041] Negative electrode sheet
[0042] In this application, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.
[0043] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0044] In some embodiments, the silicon-based material particles include one or more of silicon oxide compounds and silicon-carbon composites. Silicon-based material particles have high specific capacity, and the addition of these types of silicon-based material particles is beneficial for improving the energy density of the electrochemical device.
[0045] In some embodiments, the silicon-based material particles include a silicon-carbon composite, wherein the silicon-carbon composite comprises porous carbon and silicon-containing material dispersed in the pores of the porous carbon. The porous carbon, as a carrier for the silicon-containing material, provides support for the silicon-containing material, while the pores of the porous carbon provide space for the expansion of the silicon particles, thereby effectively alleviating the stress compression caused by the expansion of the silicon particles during charging.
[0046] In some embodiments, the mass fraction of silicon-based material particles in the negative electrode film is 0.5%-10%. Silicon-based material particles have high specific capacity, which can improve the energy density of the electrochemical device. When the mass fraction of silicon-based material particles in the negative electrode film is within the above range, the negative electrode film can have suitable space to accommodate graphite material particles. Graphite material particles have small volume changes during charge and discharge, and can act as a buffer material to reduce electrode cracking and pulverization caused by silicon expansion, thereby improving the cycle performance of the electrochemical device. Therefore, the above design is beneficial for the electrochemical device to balance energy density and cycle performance. Exemplarily, the mass fraction of silicon-based material particles in the negative electrode film is 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value between two of these.
[0047] In some embodiments, the negative electrode current collector can be a metal foil or a composite current collector. For example, copper foil can be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0048] In some embodiments, the negative electrode film further includes a conductive agent, the mass fraction of which is less than or equal to 3%. In this application, because the negative electrode film includes carbon nanotubes distributed between silicon-based material particles and graphite material particles, and distributed between silicon-based material particles, the carbon nanotubes can compensate for the poor conductivity of silicon-based material particles. Even if the mass fraction of the conductive agent in the negative electrode film is less than or equal to 3%, the negative electrode film can still maintain a high electronic and ionic conductivity. Exemplarily, the mass fraction of the conductive agent in the negative electrode film is 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or any value between two such values.
[0049] In some embodiments, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, graphene, and carbon nanofibers.
[0050] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethyl methacrylate (PMMA), and carboxymethyl chitosan (CMCS).
[0051] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0052] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0053] Positive electrode sheet
[0054] In this application, the positive electrode sheet includes a positive current collector and a positive electrode film layer disposed on at least one side surface of the positive current collector, the positive electrode film layer including a phosphate positive electrode active material.
[0055] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0056] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0057] In some embodiments, when the electrochemical device is a lithium-ion battery, the positive electrode active material may be a positive electrode active material known in the art for lithium-ion batteries. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05 At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.
[0058] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0059] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0060] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0061] electrolytes
[0062] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0063] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0064] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0065] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0066] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0067] Separating membrane
[0068] In this application, the electrochemical device also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0069] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0070] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0071] A second aspect of this application provides a negative electrode sheet, the negative electrode sheet including a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including silicon-based material particles, graphite material particles and carbon nanotubes; the carbon nanotubes distributed between the silicon-based material particles and the graphite material particles are more numerous than the carbon nanotubes distributed between the graphite material particles, and / or, the carbon nanotubes distributed between the silicon-based material particles are more numerous than the carbon nanotubes distributed between the graphite material particles.
[0072] In some embodiments, the mass fraction of carbon nanotubes is 0.01%-1%, based on the sum of silicon-based material particles and carbon nanotubes.
[0073] In some embodiments, the mass fraction of carbon nanotubes is 0.1%-0.5% of the total silicon-based material particles and carbon nanotubes.
[0074] In some implementations, the diameter of the carbon nanotubes is 0.4 nm to 3 nm.
[0075] Example 1
[0076] The preparation method of the electrochemical device is as follows:
[0077] (1) Preparation of negative electrode sheet
[0078] a. Mix single-walled carbon nanotubes, binder (polyacrylic acid), and silicon-based material particles (silicon-carbon composite) at a mass ratio of 0.5:1:98.5. Then disperse the mixture in ultrapure water with a total solid content of 30% and dry it at 180°C by spray drying to obtain a silicon-carbon composite with single-walled carbon nanotubes attached to its surface.
[0079] b. The silicon-carbon composite with single-walled carbon nanotubes attached to its surface, graphite material particles (artificial graphite), conductive agent (conductive carbon black), and binder (polyacrylic acid) prepared above are mixed in the solvent N-methylpyrrolidone at a weight ratio of 5:91:1:3, dispersed at 2500 rpm for 90 s, and the dispersion is repeated three times. After homogenization, the slurry is left to stand for 2 h to obtain the negative electrode slurry.
[0080] The negative electrode slurry was then dispersed again at 2500 rpm. Copper foil was used as the negative electrode current collector, and the negative electrode slurry was coated onto both sides of the current collector. After drying, cold pressing, cutting, and slitting, the negative electrode sheet was prepared with an areal density of 2.0 g / cm³. 2 The compacted density is 1.3 g / cm³. 3 .
[0081] The parameters of the negative electrode plate were tested using the following method:
[0082] Scanning electron microscopy (SEM) testing
[0083] The negative electrode sheet was tested using SEM to obtain its microstructure.
[0084] Figure 2 This is a scanning electron microscope image of the negative electrode sheet prepared in Example 1. Figure 3 It shows Figure 2 A magnified view of a portion of region A in the middle. (Combined with...) Figure 2 and Figure 3 It can be seen that carbon nanotubes are mainly distributed between silicon-based material particles and between silicon-based material particles and graphite material particles.
[0085] (2) Preparation of positive electrode sheet
[0086] Lithium nickel cobalt manganese oxide (LiNi) is used as the positive electrode active material. 0.5 Co 0.3 Mn 0.2 O2, conductive agent (conductive carbon black), and binder (polyvinylidene fluoride) are mixed in solvent N-methylpyrrolidone at a weight ratio of 97.6:1.4:1 and stirred evenly to obtain positive electrode slurry;
[0087] A 12μm thick aluminum foil was used as the positive electrode current collector. The positive electrode slurry was coated on both sides of the positive electrode current collector. After drying, cold pressing, cutting and slitting, the positive electrode sheet was prepared.
[0088] (3) Preparation of electrolytes
[0089] In an argon atmosphere, ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) are mixed as a solvent, and then fluoroethylene carbonate (FEC) and vinylene carbonate (VC) are added to the solvent to obtain an electrolyte. The mass ratio of ethylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, and vinylene carbonate is 0.3:0.3:0.3:0.07:0.03.
[0090] (4) Separating membrane
[0091] A 9μm thick polypropylene film was used as the separator.
[0092] (5) Assembly of electrochemical devices
[0093] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes. The stacked positive electrode, separator, and negative electrode are then placed in an aluminum-plastic film and baked under vacuum at 95°C for 24 hours. The prepared electrolyte is then injected, and the device undergoes vacuum sealing, settling, formation, and shaping processes to obtain the electrochemical device.
[0094] After the obtained electrochemical device was allowed to stand for 12 hours, its performance was tested using the following method:
[0095] Cyclic performance test:
[0096] At 25°C, the electrochemical device prepared in Example 1 was charged at a constant current of 0.1C to 3.85V, then charged at a constant voltage of 0.33C to 4.25V, and discharged at 0.33C to 2.5V, which constituted the first cycle. The discharge capacity of the first cycle was recorded as C0. The aforementioned charge-discharge cycle was repeated until the discharge capacity decreased to 80% of C0, and the number of cycles the battery had completed at this point was recorded.
[0097] Comparative Example 1
[0098] The electrochemical device was prepared using the same method as in Example 1, except that the preparation process of the negative electrode included:
[0099] Silicon-carbon composite, artificial graphite, conductive carbon black, and polyacrylic acid were mixed in the solvent N-methylpyrrolidone at a weight ratio of 5:91:1:3. The mixture was dispersed at 2500 rpm for 90 s and the dispersion was repeated three times. After homogenization, the slurry was left to stand for 2 h to obtain the negative electrode slurry.
[0100] Comparative Example 2
[0101] The electrochemical device was prepared using the same method as in Example 1, except that the preparation process of the negative electrode included:
[0102] Silicon-carbon composite, carbon nanotubes, artificial graphite, conductive carbon black, and polyacrylic acid were mixed in the solvent N-methylpyrrolidone at a weight ratio of 4.925:0.025:91:1:3.05. The mixture was dispersed at 2500 rpm for 90 s and the dispersion was repeated three times. After homogenization, the slurry was left to stand for 2 h to obtain the negative electrode slurry.
[0103] The negative electrode active material and negative electrode sheet in Comparative Examples 1 and 2 were tested using the same test method as in Example 1, and the performance of the electrochemical device was tested. The test results are shown in Table 1 below.
[0104] Table 1
[0105]
[0106] The mass fraction of carbon nanotubes in Table 1 represents the mass fraction of carbon nanotubes as a sum of silicon-based material particles and carbon nanotubes.
[0107] As can be seen from the data in Table 1, compared with Comparative Example 1 (no carbon nanotubes in the negative electrode film) and Comparative Example 2 (carbon nanotubes are directly added to the negative electrode film), in Example 1, the carbon nanotubes are mainly distributed between silicon-based material particles and between silicon-based material particles and graphite material particles, thereby the electrochemical device has improved cycle performance.
[0108] Example 2
[0109] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the negative electrode, the mass ratio of single-walled carbon nanotubes, polyacrylic acid, and silicon-carbon composite was adjusted from 0.5:1:98.5 to 0.1:1:98.9 in step a.
[0110] Example 3
[0111] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the first negative electrode active material, the mass ratio of single-walled carbon nanotubes, polyacrylic acid, and silicon-carbon composite was adjusted from 0.5:1:98.5 to 0.01:1:98.99 in step a.
[0112] Example 4
[0113] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the first negative electrode active material, the mass ratio of single-walled carbon nanotubes, polyacrylic acid, and silicon-carbon composite was adjusted from 0.5:1:98.5 to 1:1:98 in step a.
[0114] Example 5
[0115] The electrochemical device was prepared using the same method as in Example 1, except that the preparation process of the negative electrode included:
[0116] The silicon-carbon composite with single-walled carbon nanotubes attached to its surface, graphite material particles (artificial graphite), and binder (polyacrylic acid) prepared above were mixed in the solvent N-methylpyrrolidone at a weight ratio of 5:92:3. The mixture was dispersed at 2500 rpm for 90 s and the dispersion was repeated three times. After homogenization, the slurry was left to stand for 2 h to obtain the negative electrode slurry.
[0117] Example 6
[0118] The electrochemical device was prepared using the same method as in Example 1, except that the preparation process of the negative electrode included:
[0119] The silicon-carbon composite with single-walled carbon nanotubes attached to its surface, graphite particles (artificial graphite), conductive agent (conductive carbon black), and binder (polyacrylic acid) prepared above were mixed in the solvent N-methylpyrrolidone at a weight ratio of 5:89:3:3. The mixture was dispersed at 2500 rpm for 90 s and the dispersion was repeated three times. After homogenization, the slurry was left to stand for 2 h to obtain the negative electrode slurry.
[0120] Example 7
[0121] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the first negative electrode active material, in step a, the single-walled carbon nanotubes with a diameter of 1.6 nm were replaced with single-walled carbon nanotubes with a diameter of 0.4 nm.
[0122] Example 8
[0123] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the first negative electrode active material, in step a, the single-walled carbon nanotubes with a diameter of 1.6 nm were replaced with single-walled carbon nanotubes with a diameter of 3 nm.
[0124] The negative electrode plates in Examples 2 to 8 were tested using the same testing methods as in Example 1, and the electrochemical devices were also tested. The test results are shown in Table 2 below. For ease of comparison, the test results of Example 1 are also shown.
[0125] Table 2
[0126]
[0127] In Table 2, the mass fraction of carbon nanotubes represents the sum of silicon-based material particles and carbon nanotubes. The mass fraction of conductive agent represents the mass fraction of conductive agent in the negative electrode film.
[0128] As can be seen from the data in Table 2, when the total mass fraction of silicon-based material particles and carbon nanotubes is 0.01%-1%, the diameter of the carbon nanotubes is 0.4nm-3nm, and the mass fraction of the conductive agent in the negative electrode film is 0%-3%, the prepared electrochemical device exhibits improved cycle performance. In particular, when the total mass fraction of silicon-based material particles and carbon nanotubes is 0.1%-0.5%, the cycle performance of the prepared electrochemical device is further improved, while maintaining energy density.
[0129] Example 9
[0130] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the negative electrode, the single-walled carbon nanotubes in Example 1 were replaced with few-walled carbon nanotubes in step a.
[0131] Example 10
[0132] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the negative electrode, in step a, the single-walled carbon nanotubes in Example 1 were replaced with multi-walled carbon nanotubes.
[0133] Example 11
[0134] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the negative electrode, in step a, the silicon-based material particle silicon-carbon composite in Example 1 was replaced with silicon suboxide.
[0135] The negative electrode plates in Examples 9 to 11 were tested using the same testing methods as in Example 1, and the performance of the electrochemical devices was tested. The test results are shown in Table 3 below. For ease of comparison, the test results of Example 1 are also shown.
[0136] Table 3
[0137]
[0138] As can be seen from the data in Table 3, the electrochemical device obtained by using the above-mentioned types of carbon nanotubes and silicon-based material particles has improved cycle performance.
[0139] Example 12
[0140] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the negative electrode, in step b, the silicon-carbon composite with single-walled carbon nanotubes attached to its surface, graphite material particles (artificial graphite), conductive agent (conductive carbon black), and binder (polyacrylic acid) prepared above were mixed in the solvent N-methylpyrrolidone at a weight ratio of 0.51:95.49:1:3, dispersed at 2500 rpm for 90 s, and the dispersion was repeated three times. After homogenization, the slurry was left to stand for 2 h to obtain the negative electrode slurry.
[0141] Example 13
[0142] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the negative electrode, in step b, the silicon-carbon composite with single-walled carbon nanotubes attached to its surface, graphite material particles (artificial graphite), conductive agent (conductive carbon black), and binder (polyacrylic acid) prepared above were mixed in the solvent N-methylpyrrolidone at a weight ratio of 10.2:85.8:1:3, dispersed at 2500 rpm for 90 s, and the dispersion was repeated three times. After homogenization, the slurry was left to stand for 2 h to obtain the negative electrode slurry.
[0143] The negative electrode plates in Examples 12 and 13 were tested using the same testing methods as in Example 1, and the performance of the electrochemical devices was tested. The test results are shown in Table 4 below. For ease of comparison, the test results of Example 1 are also shown.
[0144] Table 4
[0145]
[0146] The mass fraction of silicon-based material particles in Table 4 represents the mass fraction of silicon-based material particles in the negative electrode film layer.
[0147] As can be seen from the data in Table 4, when the mass fraction of silicon-based material particles in the negative electrode film is 0.5%-10%, the resulting electrochemical device has improved cycle performance.
[0148] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. An electrochemical device, characterized in that, The electrochemical device includes an electrolyte, a positive electrode, and a negative electrode, wherein the negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector. The negative electrode film layer includes silicon-based material particles, graphite material particles, and carbon nanotubes; The number of carbon nanotubes distributed between the silicon-based material particles and the graphite material particles is greater than the number of carbon nanotubes distributed between the graphite material particles, and / or, There are more carbon nanotubes distributed between the silicon-based material particles than between the graphite material particles.
2. The electrochemical device according to claim 1, characterized in that, The mass fraction of the carbon nanotubes is 0.01%-1%, calculated as the sum of the silicon-based material particles and the carbon nanotubes.
3. The electrochemical device according to claim 2, characterized in that, The mass fraction of the carbon nanotubes is 0.1%-0.5%, calculated as the sum of the silicon-based material particles and the carbon nanotubes.
4. The electrochemical device according to any one of claims 1 to 3, characterized in that, The carbon nanotubes include one or more of single-walled carbon nanotubes, few-walled carbon nanotubes, and multi-walled carbon nanotubes.
5. The electrochemical device according to any one of claims 1 to 4, characterized in that, The diameter of the carbon nanotubes is 0.4 nm to 3 nm.
6. The electrochemical device according to any one of claims 1 to 5, characterized in that, The silicon-based material particles include one or more of silicon oxide compounds and silicon-carbon composites.
7. The electrochemical device according to any one of claims 1 to 6, characterized in that, The mass fraction of the silicon-based material particles in the negative electrode film is 0.5%-10%.
8. The electrochemical device according to any one of claims 1 to 7, characterized in that, The negative electrode film layer also includes a conductive agent, wherein the mass fraction of the conductive agent in the negative electrode film layer is less than or equal to 3%.
9. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector; The negative electrode film layer includes silicon-based material particles, graphite material particles, and carbon nanotubes; The number of carbon nanotubes distributed between the silicon-based material particles and the graphite material particles is greater than the number of carbon nanotubes distributed between the graphite material particles, and / or, There are more carbon nanotubes distributed between the silicon-based material particles than between the graphite material particles.
10. The negative electrode sheet according to claim 9, characterized in that, The mass fraction of the carbon nanotubes is 0.01%-1%, calculated as the sum of the silicon-based material particles and the carbon nanotubes.
11. The negative electrode sheet according to claim 10, characterized in that, The mass fraction of the carbon nanotubes is 0.1%-0.5%, calculated as the sum of the silicon-based material particles and the carbon nanotubes.
12. The negative electrode sheet according to any one of claims 9 to 11, characterized in that, The diameter of the carbon nanotubes is 0.4 nm to 3 nm.
